Sikap Pelayan Tuhan dalam Menghadapi Penderitaan yang Tidak Harus Dia Tanggung; Refleksi Surat 1 Petrus 2:18-25 - Tilaar, Stenny Spencer (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2022)
There are two main problems when Servants of God face suffering. 1) they are the source of problem; 2) they respond it by retaliating for the unfair action. This is different from Peter’s statement that said, “For it is a grace if a person is knowingly bear the suffering he does not have to.” In researching for this discussion, the interpretation method of the epistles are used, namely, the historical and cultural background of the text and the explanation based on the structure of the text. This point related to the theme of the epistle of Peter 1 which has the background of suffering because of injustice, and also related to a slave who shows that he belongs to his master. Slaves are suffering from injustice, but Christ has set an example for the suffering of injustice. In addition, the work of Christ on the cross also has aimed for the people to die to sin and live for righteousness. To die to sin is to live by doing good things, and to live for righteousness is to be given the ability to endure the suffering of injustice. For Christ’s example is universal, then God’s ministers are also should die to sin, given the ability to live in righteousness and not suffer by their own mistakes. The purpose of this research is to see abilty of the servant of God when endure the suffering of injustice.